Legitimacy of control - Wendelin Schnedler; Radovan Vadovic (Institute for the Study of Labor (IZA), 2007)
What is the motivational effect of imposing a minimum effort requirement? Agents may no longer exert voluntary effort but merely meet the requirement. Here, we examine how such hidden costs of control change when control is considered legitimate. We study a principal-agent model where control signals the expectations of the principal and the agent meets these expectations because he is guilt-averse. We conjecture that control is more likely to be considered legitimate (i) if it is not exclusively aimed at a specific agent or (ii) if it protects the endowment of the principal. Given the conjecture, the model predicts that hidden costs are lower when one of the two conditions is met. We experimentally test these predictions and find them confirmed.
Keywords: 330; Moral hazard; intrinsic motivation; guilt aversion; Leistungskontrolle; Agency Theory; Moral Hazard; Leistungsmotivation; Theorie